Calculated Parameters of Thyroid Homeostasis: Emerging Tools for Differential Diagnosis and Clinical Research - Dietrich, Johannes W.; Landgrafe-Mende, Gabi; Wiora, Evelin; Chatzitomaris, Apostolos; Klein, Harald H.; Midgley, John E. M.; Hoermann, Rudolf (Frontiers in Endocrinology, 2016)
Although technical problems of thyroid testing have largely been resolved by modern assay technology, biological variation remains a challenge. This applies to subclinical thyroid disease, non-thyroidal illness syndrome and those 10% of hypothyroid patients, who report impaired quality of life despite normal thyrotropin (TSH) concentrations under L-T4 replacement. Among multiple explanations for this condition inadequate treatment dosage and monotherapy with L-T4 in subjects with impaired deiodination have received major attention. Translation to clinical practice is difficult, however, since univariate reference ranges for TSH and thyroid hormones fail to deliver robust decision algorithms for therapeutic interventions in patients with more subtle thyroid dysfunctions. Advances in mathematical and simulative modelling of pituitary-thyroid feedback control have improved our understanding of physiological mechanisms governing the homeostatic behaviour. From multiple cybernetic models developed since 1956, four examples have also been translated to applications in medical decision-making and clinical trials. Structure parameters representing fundamental properties of the processing structure include the calculated secretory capacity of the thyroid gland (SPINA-GT), sum activity of peripheral deiodinases (SPINA-GD), Jostel’s TSH index for assessment of thyrotropic pituitary function and a recently published algorithm for reconstructing the personal set point of thyroid homeostasis. In addition, a family of integrated models (UCLA platform) provides advanced methods for bioequivalence studies. This perspective article delivers an overview of current clinical research on the basis of mathematical thyroid models. In addition to a summary of large clinical trials it provides previously unpublished results of validation studies based on simulation and clinical samples.